Vaccines for COVID-19: A Systematic Review of Immunogenicity, Current Development, and Future Prospects - Zhang, Zhan; Shen, Qi; Chang, Haocai (Frontiers in Immunology, 2022)
The persistent coronavirus disease 2019 (COVID-19), characterized by severe respiratory syndrome, is brought on by coronavirus 2 (SARS-CoV-2), and it poses a major health challenge to people all over the world. Currently, optimal COVID-19 management involves effective vaccination. Vaccination was shown to greatly enhance immune response against viral infections and reduce public transmission of COVID-19. However, although current vaccines offer some benefits, viral variations and other factors demand the continuous development of vaccines to eliminate this virus from host. Hence, vaccine research and development is crucial and urgent to the elimination of this pandemic. Herein, we summarized the structural and replicatory features of SARS-CoV-2, and focused on vaccine-mediated disease prevention strategies like vaccine antigen selection, vaccine research, and vaccine application. We also evaluated the latest literature on COVID-19 and extensively reviewed action mechanisms, clinical trial (CT) progresses, advantages, and disadvantages of various vaccine candidates against SARS-CoV-2. Lastly, we discussed the current viral treatment and prevention trends and future prospects.